Performance of Radiative Transfer Models in the Microwave Region. Issue 6 (26th March 2020) - Moradi, Isaac; Goldberg, Mitchell; Brath, Manfred; Ferraro, Ralph; Buehler, Stefan A.; Saunders, Roger; Sun, Ninghai
Abstract: We compared two fast radiative transfer models, Community Radiative Transfer Model (CRTM) and Radiative Transfer for TIROS Operational Vertical Sounder (RTTOV), with the LBL model Atmospheric Radiative Transfer Simulator (ARTS). We used the measurements from Advanced Technology Microwave Sounder (ATMS) and the Global Precipitation Measurement Microwave Imager (GMI) for evaluation of the radiative transfer models. The models in comparison with the observations and each other performed very well with a mean difference less than 0.5 K for the temperature sounding channels operating near the oxygen absorption band at 60 GHz. There was a difference of up to 1 K among the models as well as compared with the observations for humidity sounding channels operating around water vapor absorption line at 183 GHz. The mean difference between the simulations and observations was up to 6 K for surface sensitive channels. Water vapor and surface sensitive channels also showed to be more sensitive than the temperature sounding channels to the spectroscopy models used to calculate the absorption coefficients. There was a small difference, less than 0.1 K, between brightness temperatures calculated using traditional boxcar and actual Sensor or Spectral Response Functions, except for a difference of 0.25 K for ATMS Channel 6. Double difference technique showed about 1 K difference between water vapor channels from ATMS instruments onboard N20 and National Polar‐orbiting Partnership (NPP). However, comparison of a new version of ATMS/NPP observations recently generated using an enhanced calibration algorithm with ATMS/N20 observations showed that the differences between the two instruments are less than 0.5 K after improving the ATMS/NPP calibration. Plain Language Summary: Radiative transfer models are used to simulate satellite observations from input atmospheric profiles and surface parameters. These models have a wide range of applications, including being used as forward model to assimilate satellite observations into numerical weather prediction models or for calibration and validation of satellite measurements. Radiative transfer models are subject to errors and uncertainties and therefore need to be evaluated. We compared three microwave radiative transfer models versus each other as well as satellite measurements. The results showed that the models were consistent with each other and with observations for microwave temperature sounding channels. However, the models were less consistent with each other and with the observations for the water vapor and window channels. The difference between the models and observations was affected by several factors such as spectral response functions, spectroscopy databases, and emissivity models. Key Points: Microwave radiative transfer models generally agree with each other and observations Spectroscopy models largely impact simulations for window and water vapor channels Sensor response function and emissivity show some important effect on calculated brightness temperatures